Breaking self‐tolerance during autoimmunity and cancer immunity: Myeloid cells and type I IFN response regulation. Issue 6 (2nd February 2018) - Tarbell, Kristin V.; Egen, Jackson G.
Abstract: The generation and regulation of innate immune signals are key determinants of autoimmune pathogenesis. Emerging evidence suggests that parallel processes operating in the setting of solid tumors can similarly determine the balance between tolerance and immunity and ultimately the effectiveness of the antitumor immune response. In both contexts, self‐specific responses start with innate immune cell activation that leads to the initial break in self‐tolerance, which can be followed by immune response amplification and maturation through innate‐adaptive crosstalk, and finally immune‐mediated tissue/tumor destruction that can further potentiate inflammation. Of particular importance for these processes is type I IFN, which is induced in response to endogenous ligands, such as self‐nucleic acids, and acts on myeloid cells to promote the expansion of autoreactive or tumor‐specific T cells and their influx into the target tissue. Evidence from the study of human disease pathophysiology and genetics and mouse models of disease has revealed an extensive and complex network of negative regulatory pathways that has evolved to restrain type I IFN production and activity. Here, we review the overlapping features of self‐ and tumor‐specific immune responses, including the central role that regulators of the type I IFN response and innate immune cell activation play in maintaining tolerance, and discuss how a better understanding of the pathophysiology of autoimmunity can help to identify new approaches to promote immune‐mediated tumor destruction. Abstract : Review of innate immune regulation in both cancer and autoimmune disease pathogenesis, with a focus on the function and regulation of type 1 IFN responses.